SOFT MODEL PENGUATAN KINERJA WIRAUSAHA MUDA - Muhamad Nuris Salam; Rauly Sijabat (STIE Pelita Nusantara Semarang, 2021)
Business performance ranging from the number of turnovers that do not grow, the number of customers that are not growing, profits that do not increase and sales that remain are classic problems faced by small and micro businesses, including the Youth Entrepreneurial Group (KWP) assisted by the Central Java Province Dinpora. This condition is caused by the limited capabilities of human resource competencies, the capabilities of financial factors and operational factors. This phenomenon is the basis for this study to conduct a study of the factors of strength, weakness, opportunity, and threat to then identify the variables that explain KWP's marketing performance. The research was conducted on business owners who are Youth Entrepreneurs Group (KWP) assisted by the Central Java Province Dinpora. Henceforth, the field data was analyzed using several qualitative approaches which were carried out with SWOT and AHP analysis as well as a quantitative approach to obtain a more complete insight. The results of the analysis show that external factors such as the role of government, the business environment and access to information contribute to building the internal strength of business groups which include financial factors, management factors and operational factors.